"Push" and "Pull" Moves in Hispanic and Swedish Negotiation Talk - Lars Fant (Hermes, 1993)
In negotiations recorded on video-tape under near-identical conditions in Mexico, Spain and Sweden, two types of action were studied, defined as (1) affirming one's own party's position or image ("push"), and (2) attracting the other party by means of strengthening that party's position and image, or by underscoring the bonds between each parties ("pull"). A tentative typology of "push" vs. "pull" moves is proposed, including three mixed types, which are named "disguised", "linked" and "ambiguous" push/pull moves. The three nationality groups are compared in terms of the suggested typology, and analogous features are found between conversational analysis data and sociological/anthropological reports on Scandinavian, Spanish and Mexican culture.